Study on the evolution of tourism and perspectives - Ștefan Virgil IACOB (Theoretical and Applied Economics, 2020)

(untitled)
Tourism is one of the important branches of the national economy in most countries, but first of all it is important for Romania. In the process of restructuring and reorganization of the national economy after 1990, unfortunately they did not seek to maintain areas in which Romania had sufficient expertise, experience gained to remain priority areas for us, but also for the European Union or more broadly and it has reached a situation where the industry has been practically destroyed, agriculture is left to chance and moreover, no support is given for the development of certain branches. Tourism is the one in which Romania, naturally having a proportional structure and a very important historical past, has possibilities to develop a large-scale tourism. Agrotourism, traditional resorts, privatization in the field of tourism and many more must give a definite perspective for the future evolution of this activity. When we discuss the situation that happened until December 31, 2019, we have in mind the fact that certain measures have been taken, left-handed is true, but in which tourism continued to be one of the branches that was in full development and had the opportunity to contribute and in the future to a greater extent in the formation of the Gross Domestic Product. Unfortunately, at the time of writing this article, we are in the midst of a pandemic, caused by the coronavirus crisis (COVID 19), in which the perspective of tourism evolution is practically strangled. We are considering the suspension of this activity altogether, as domestic tourism or external tourism. We are also considering moving to technical unemployment and perhaps from now on, unemployment and other forms of unemployment. Until January 2020, there were increases in most indicators and here we mention arrivals, overnight stays and the number of tourists per structure. The structural analysis of the number of tourists was done monthly or quarterly, as well as a broader analysis attempt. At the same time, the perspective of improving the structure of Romanian tourism, increasing accommodation capacity, quality of life and so on was taken into account. This article is written at a turning point, between what was until December 31, 2019, if you want until February 29, 2020 in a way, in the evolution of tourism in our country and what is seen in conjunction with this pandemic, after which will follow without a doubt and perhaps a special economic and financial crisis. The economic and financial crisis has already affected domestic tourism owners and will continue to affect them if they are not supported by government measures. We must also have a point of view regarding the role of the European Union in ensuring the takeover of the activity in this field, which suffers not only Romania, but also in all the member countries of the European Union or its non-members, as well as in terms of world.